ADOPTION OF SOCIABLE GREEN ENGINEERING FOR SUSTAINABLE DEVELOPMENT - Bhonde, Prakash Janardan (European Scientific Journal, ESJ, 2015)
India is striding ahead to become a world leader in manufacturing of ferrous metals & alloys. Rapid globalization has driven up-gradation to its ultra-modern infra-structure. It has contributed to India’s sustainable industrial growth in auto, infra, mining, petrochemicals, and power sectors. Hence over the decade, its per capita consumption of ferrous products has vastly increased. Existing units of iron and steel manufacturing industries emit the greenhouse gases (GHG) with variable life span with multiple and Global Warming Potential (GWP). These are responsible for the global climate changes. Global Warming & negligence of integrated impact of enviro-scoio-human-economic factors while achieving technological progress has today become the greatest challenge to the human endeavor for its continued and dignified existence on this planet. Clean Development Mechanism (CDM), which is multistage knowledge process is one of the ways identified under the KYOTO Protocol, for developed countries to offset their carbon emissions, is fast becoming the preferred way.Moreover, KYOTO protocol based market driven generation, registration, valuation of carbon credit and its subsequent trading leads to penalize the polluting and reward the clean industries. Consequently, authors have attempted to create awareness among the ferrous metal manufacturing industries to minimize the hazardous impact of GHG by investing in modernization of various sections, machineries and process of the integrated plants by discussing a few case studies and methodologies adopted to translate controlling carbon emission into a profit churning venture. Implementing alternative, appropriate, innovative, resource conserving, safe & green technology will lead to sustainable development.